MATHEMATICAL MODELING AND FORECASTING METHODS BASED ON SENSOR DATA FOR MONITORING THE TECHNICAL CONDITION OF BUILDINGS AND STRUCTURES (Eureka Journal of Civil, Architecture and Urban Studies, 2025)
In recent years, the issue of reliable assessment of the technical condition of buildings and structures during operation has become one of the most pressing challenges. Traditional visual inspections and periodic surveys are insufficient for identifying structural changes that occur in real time. This article analyzes mathematical modeling and forecasting methods based on modern sensor systems for monitoring the technical condition of buildings and structures. In the study, deformation, stress, vibration, and deterioration processes are described using mathematical equations. The obtained results demonstrate that the proposed approach enables early assessment of the technical condition and timely detection of potentially hazardous states.
Keywords: technical condition monitoring, sensor systems, mathematical modeling, deformation, dynamic analysis, forecasting.